Parametric Analysis of a Universal Isotherm Model to Tailor Characteristics of Solid Desiccants for Dehumidification - Burhan, Muhammad; Chen, Qian; Shahzad, Muhammad Wakil; Ja, M Kum; Ng, Kim Choon (Frontiers in Energy Research, 2022)
Cooling has a significant share in energy consumption, especially in hot tropical regions. The conventional mechanical vapor compression (MVC) cycle, widely used for air-conditioning needs, has high energy consumption as air is cooled down to a dew point to remove the moisture. Decoupling the latent cooling load through dehumidification from the sensible cooling load can significantly improve the energy requirement for air-conditioning applications. Solid desiccants have shown safe and reliable operation against liquid desiccants, and several configurations of solid desiccants dehumidifiers are studied to improve their performance. However, the characteristics of solid desiccants are critical for the performance and overall operation of the dehumidifier. The properties of every desiccant depend upon its porous adsorbing surface characteristics. Hence, it has an optimum performance for certain humid conditions. Therefore, for a better dehumidification performance in a specific tropical region, the solid desiccant must have the best performance, according to the humidity range of that region. In this article, a theoretical methodology has been discussed to help the industry and chemists to understand the porous structural properties of adsorbent surfaces needed to tune the material performance for a particular humidity value before material synthesis.